ANALISIS INTEGRASI PASAR DAN PERMINTAAN LADA INDONESIA DI PASAR DUNIA - , ENDAH NURAINI, Prof.Dr.Ir. Dwidjono Hadi Darwanto, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study was aimed to: (1) determine market integration and causality between domestic and international market of pepper, (2) estimate domestic demand for pepper and (3) investigate position of Indonesia as exporter of pepper in the world market. Johansen cointegration analysis and the Engle-Granger approach were applied in analyzing of long-run integration between Indonesia âs market to other exporters and importers of pepper. Granger causality test was applied to determine the causal relationship between market prices and the price leader country while Error Correction Model (ECM) Test was also applied to determine the short-run integration between Indonesiaâs pepper market with other exporters and importers market. Then, Ordinary Least Square (OLS) to determine the factors that influence the demand for pepper exports of Indonesia and analysis of Trade Specialization Index (ISP) was applied to analize Indonesia's position as exporter of pepper in the world market. Annually time series data during the period of 1980 â 2009 were used in analyses. The results of study show that: (1) there is a long-run and short-run integration between Indonesiaâs market with other exporters or importers of pepper